Impact of evaporative cooling due to wetting of urban materials on local thermal comfort in a street canyon. (August 2019) - Kubilay, A.; Derome, D.; Carmeliet, J.
Highlights: Evaporative-cooling potential of pavements and resulting thermal comfort are analyzed. Cooling potential depends on moisture permeability, moisture capacity and thermal diffusivity. An increase in wetting amount extends the duration of evaporative cooling. Increasing wetting has no impact on maximum reduction in surface temperature. By controlling wetting period, cooling potential can be increased by about 20%. Abstract: The choice of urban materials strongly influences the outdoor thermal comfort through their role in the absorption, transport and storage of heat and moisture. The present study investigates the level of evaporative cooling reached after rain events of varying intensities using urban materials with distinct thermal and moisture transport properties. Further, the resulting impact on thermal comfort is studied. The local climate in a street canyon is modeled using a fully-integrated model that couples computational fluid dynamics (CFD) simulations of wind flow with the three-dimensional heat and moisture transport (HAM) in porous urban materials. Wetting due to rain deposition on each surface is calculated using an Eulerian multiphase wind-driven rain model. The results show that an increase in the rainfall intensity extends the effective duration of evaporative cooling, but does not change the reduction in maximum surface temperatures. The improvement in the thermal comfort in the street canyon depends on a combination of factors such as moisture permeability, moisture capacity and thermal diffusivity of materials.